The Impact of a Single Dual-Trained Surgeon in the Management of Mastectomy and Reconstruction. Issue 4 (31st January 2022) - Piper, Merisa L.; Nathan, Shelby; Henderson, Stacy; Lee, Alfred; Broach, Robyn B.; Kozak, Geoffrey; Davis, Harrison; Wu, Liza C.
Abstract : Background: Oncoplastic breast surgery is typically performed using a two-surgeon, two-team approach. The authors present their experience with patients undergoing mastectomy and immediate reconstruction performed by a single, dual-trained breast surgical oncologist and plastic and reconstructive microsurgeon. Methods: Patients who underwent mastectomy and/or immediate reconstruction performed by the senior author between 2015 and 2019 were divided into single-surgeon or dual-surgeon cohorts, and matched by age, body mass index, reconstruction type, and cancer stage. Results: The authors included 158 patients in their analysis (single-surgeon, n = 45; dual-surgeon, n = 113). Single-surgeon patients underwent surgery 13.2 days earlier than dual-surgeon patients ( p < 0.01), and required significantly fewer preoperative (1.9 versus 3.4; p < 0.01) and postoperative visits (6.8 versus 10.7; p < 0.01). Operative duration was comparable (single-surgeon, 245 minutes; dual-surgeon, 245 minutes; p = 0.99). The authors found no significant difference in surgical-site infection, seroma, hematoma, abdominal donor-site healing, or flap and prosthesis loss between the groups. The authors did find that dual-surgeon patients had a significantly higher rate of mastectomy flap necrosis (20 percent versus 4 percent; p = 0.01), which held true on logistic regression when controlling for other variables. BREAST-Q data demonstrated that single-surgeon patients had significantly higher overall scores ( p = 0.04), and were significantly more satisfied with their outcomes, surgeon, and the information provided ( p = 0.03, p = 0.03, and p = 0.01, respectively). Conclusions: The single-surgeon approach has the potential to decrease patient burden by requiring fewer preoperative and postoperative visits without compromising surgical outcomes or oncologic safety. Further investigation is warranted into the financial implications and patient outcomes. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.